High-Throughput Functional Genetic and Compound Screens Identify Targets for Senescence Induction in Cancer - Wang, Liqin; Leite de Oliveira, Rodrigo; Wang, Cun; Fernandes Neto, João M.; Mainardi, Sara; Evers, Bastiaan; Lieftink, Cor; Morris, Ben; Jochems, Fleur; Willemsen, Lisa; Beijersbergen, Roderick L.; Bernards, René (Cell reports (Cambridge), 2017)
Senescence is a proliferation arrest that can result from a variety of stresses. Cancer cells can also undergo senescence, but the stresses that provoke cancer cells to undergo senescence are unclear. Here, we use both functional genetic and compound screens in cancer cells harboring a reporter that is activated during senescence to find targets that induce senescence. We show that suppression of the SWI/SNF component SMARCB1 induces senescence in melanoma through strong activation of the MAP kinase pathway. From the compound screen, we identified multiple aurora kinase inhibitors as potent inducers of senescence in RAS mutant lung cancer. Senescent melanoma and lung cancer cells acquire sensitivity to the BCL2 family inhibitor ABT263. We propose a one-two punch approach for the treatment of cancer in which a drug is first used to induce senescence in cancer cells and a second drug is then used to kill senescent cancer cells. [Display omitted] •CRISPR and chemical screens identify senescence inducers in cancer cells•SMARCB1 knockout induces senescence in melanoma•Aurora kinase inhibition induces senescence in multiple cancer types•Senescent cancer cells become vulnerable to killing by ABT263 Wang et al. find that CRISPR-mediated genetic screens and chemical screens serve as two types of high-throughput methods to identify senescence inducers in cancer cells. They also show that senescent cancer cells can be killed selectively by the BCL2-family inhibitor ABT263, providing a potential sequential drug treatment strategy for cancer.